The Effect Of Work Discipline On Work Performance In The Office South Binjai Sub-District - Salamudin; Mesra B (Yayasan Multidimensi Kreatif, 2024)
This study aimed to analyze the effect of Work Discipline on Work Performance at the Binjai Selatan Subdistrict Office. This research used a quantitative causal associative method. The study was conducted with a population of 117 employees. The sampling technique used was saturated sampling, where all members of the population were included as samples. The data used were obtained from questionnaires distributed to respondents, consisting of all employees from various divisions within the office. The results showed that Work Discipline had a positive and significant effect on Work Performance. This was proven by a t-value of 13.416, which was greater than the t-table value of 1.99656, and a significance value of 0.000, which was less than 0.05. The regression coefficient of 1.267 indicated that every 1-point increase in Work Discipline would lead to an increase of 1.267 points in Work Performance, assuming other variables remained constant. Furthermore, the results of the coefficient of determination test showed an Adjusted R Square value of 0.628 or 62.8%, indicating that Work Discipline had a significant influence on Work Performance, with 37.2% influenced by other factors not included in the study. Overall, the findings of this research identified that improving Work Discipline could significantly contribute to enhancing Work Performance at the Binjai Selatan Subdistrict Office.